Survival of Salmonella typhimurium in irradiated fresh chicken halves - Aquino, Louise Callanta
ABSTRACT A survey was conducted to determine Salmonella count in fresh chicken halves obtained from three big, wet markets. After microbiological analysis using selective media, total Salmonella counts ranged from <25 to 1.17 x 10^3 cfu/g. Fresh chicken obtained from the market with the lowest Salmonella count was irradiated using Cobalt-60 as radiation source. Chicken homogenate inoculated with Salmonella typhimurium was exposed to varying doses of radiation ranging from 0.2 to 3.0 kGy to determine the D10 value. This was calculated as 2.1 kGy. To determine physico-chemical and sensory changes induced by irradiation, inoculated chicken samples were irradiated at the D10 value of S. typhimurium. Analyses were performed by comparing characteristic differences between the control and irradiated fresh chicken halves, in terms of physico-chemical changes such as texture and pH, and sensory attributes such as color and odor. The texture value of chicken increased from 54 ± 0.94 to 59 ± 0.82 mm/s, indicating a softening effect of irradiation at a dose level of 2.1 kGy. The pH slightly decreased from 6.43 ± 0.05 to 6.30 ± 0.04. Light pink discoloration of chicken meat was observed, although it was considered not objectionable. No odor change was observ